Model Kajian Implementasi Sistem Informasi Penelitian Dan Pengabdian Kepada Masyarakat Politeknik Negeri Banjarmasin - Rozaq, Abdul; Hardinto, Raden Kelik; Sholihin, Fuad (P3M Politeknik Negeri Banjarmasin, 2021)
The Center for Research and Community Service (P3M) POLIBAN is a center that has the task and function of facilitating research and community service activities carried out by lecturers at the Banjarmasin State Polytechnic. Starting in 2018, research data and community service management by developing a research and community service Information System (SIPMA). The data management starts from determining the scheme to be given funding, which includes the scope of the research, the schedule for submitting proposals, reviewing proposals to implementation and reporting. Meanwhile, to see the success rate of SIPMA implementation, P3M Poliban has not yet evaluated the SIPMA implementation. Based on the above problems, P3M Poliban requires a study of SIPMA implementation, so that it can be seen the level of success and satisfaction of SIPMA users. This study distributed a measuring instrument in the form of a questionnaire to SIPMA users. Where in the analysis process the framework for the application of Partial Least Square (PLS) is used in SEM, which is a statistical model that provides an approximate calculation of the strength of the hypothesized relationship between variables in a theoretical model. The results of the study indicate that the quality of the system has a significant effect on user satisfaction with a T-statistic of 3.107 (> 1.96). Information quality has a significant effect on User Satisfaction with a T-statistic of 2,215 (> 1.96). Service Quality has a significant effect on User Satisfaction with a T-statistic of 2.909 (> 1.96). User Satisfaction has a significant effect on Individual Impact with a T-statistic of 15.652 (> 1.96). Individual Impact has a significant effect on Organizational Impact with a T-statistic of 10,410 (> 1.96).